The prevention and treatment of exercise-induced muscle damage - Howatson, G.; van Someren, K. A. (Sports Medicine, 2008)
Exercise-induced muscle damage (EIMD) can be caused by novel or unaccustomed exercise and results in a temporary decrease in muscle force production, a rise in passive tension, increased muscle soreness and swelling, and an increase in intramuscular proteins in blood. Consequently, EIMD can have a profound effect on the ability to perform subsequent bouts of exercise and therefore adhere to an exercise training programme. A variety of interventions have been used prophylactically and/or therapeutically in an attempt to reduce the negative effects associated with EIMD. This article focuses on some of the most commonly used strategies, including nutritional and pharmacological strategies, electrical and manual therapies and exercise. Long-term supplementation with antioxidants or [beta]-hydroxy-[beta]-methylbutyrate appears to provide a prophylactic effect in reducing EIMD, as does the ingestion of protein before and following exercise. Although the administration of high-dose NSAIDs may reduce EIMD and muscle soreness, it also attenuates the adaptive processes and should therefore not be prescribed for long-term treatment of EIMD. Whilst there is some evidence that stretching and massage may reduce muscle soreness, there is little evidence indicating any performance benefits. Electrical therapies and cryotherapy offer limited effect in the treatment of EIMD; however, inconsistencies in the dose and frequency of these and other interventions may account for the lack of consensus regarding their efficacy. Both as a cause and a consequence of this, there are very few evidence-based guidelines for the application of many of these interventions. Conversely, there is unequivocal evidence that prior bouts of eccentric exercise provide a protective effect against subsequent bouts of potentially damaging exercise. Further research is warranted to elucidate the most appropriate dose and frequency of interventions to attenuate EIMD and if these interventions attenuate the adaptation process. This will both clarify the efficacy of such strategies and provide guidelines for evidence-based practice.